A review of suicidal ideation and behavior among university students: protective and risk factors associated with the prevention of suicide - Ahmad Basri, Nadzirah; Kumagai, Shuzo (Kyushu University, 2017)
This article presents a review of studies on protective and risk factors on suicidal ideation and behaviors. First, a recent theory related to suicidal behavior was introduced. Then studies reporting on prevalence of suicidal ideation and behaviors among university students were reviewed, followed by an introduction to the wide range of protective and risk factors to suicide. Next, studies on several protective and risk psychological factors were reviewed. Finally, Japanese cultural influence on suicide and initiatives made for suicide prevention in Japan were discussed.